ANALISIS PENGARUH BRAND IMAGE, SERVICE QUALITY, KEPUASAN PELANGGANDANLOYALITAS KONSUMEN RUMAH SAKIT - Cahyamas Arif Satria Pudjonarko; Farida Indriani (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
The research objective is to analyze the influence ofbrand image, service quality, customer satisfaction on loyalty to return to the hospital in Permata Medika, Semarang through service quality and customer satisfaction as interveing variable.The sampling method used in this research is non-probability sampling with a purposive sampling technique. The samples collected were 100 respondents at Permata Medika Hospital to find out information about re-visit intention in the hospital. The analytical method used is multiple analysis techniques which include validity test, reliability test, classic assumption test, multiple linear regression test, t test, f test, determination test, and sobel test.The results showed that brand image had a positive and significant effect on service quality and loyalty but negative and not significant on customer satisfaction, service quality had a positive and significant effect on customer satisfaction and loyalty, and customer satisfaction had a positive and significant effect on customer loyalty.